Pengaruh Metode Share Reading Terhadap Kemampuan Membaca Lancar Pada Peserta Didik Sanggar Belajar Kepong Malaysia - Kanaya, Meiana; Pratiwi, Indah (Jurnal Gentala Pendidikan Dasar, 2026)
Fluent reading ability is very important in education and is the most crucial basic skill for students. Even at the primary education level, students acquire basic abilities and develop the reading skills necessary for social life. The purpose of this study was to determine the effect of the share reading method on the fluent reading ability of students at the Kepong Learning Centre in Malaysia. This study is quantitative research. The research was conducted in Grade 1 with 15 students as subjects. This study was conducted in one class as an experimental class. The data collection technique in this study was observation, and the design of this study was a one-group pretest-posttest. The average pretest score was 39, which is in the not yet fluent category. After being given treatment using the shared reading method, a post-test was administered, with an average score of 71, which is in the fluent category. The t-test yielded a significance value of 0.000 < 0.05. Based on the results of the study, there is an effect of the shared reading method on the fluent reading ability of students at the Kepong Learning Centre in Malaysia.